Examining Infants’ Individuation of Others by Sociomoral Disposition - Taborda-Osorio, Hernando; Lyons, Ashley B.; Cheries, Erik W. (Frontiers in Psychology, 2019)
Early on infants seem to represent social actions of others from a moral perspective, evaluating others’ dispositions as “mean” or “nice”. The current research examined whether or not 11-month-old infants represent these sociomoral dispositions as deep and identity-determining properties using an object individuation task. Infants were shown two identical looking characters emerging sequentially from behind a screen and engaging in two different sociomoral actions. By using a looking-time paradigm the results show an interaction effect between the baseline and test trials, showing that infants seem to represent two different characters involved in the event, disregarding their same external appearance. This effect was mainly apparent when infants witnessed a negative event first in test trials. Experiments 2 and 3 control for alternative explanations. In experiment 2 infants failed to individuate two characters when they are shown two identical looking puppets. In experiment 3 infants fail to represent two characters when social information was taken away from the show. We discuss the possibility that by the end of the first year of life infants might represent sociomoral dispositions as diagnostic of individual identity.